Spatial variability of soil inorganic N in a mature oil palm plantation in Sabah, Malaysia - Abdul Rahim, Anuar; Kah, Joh Goh; Tee, Bee Heoh; Ahmed, Osumanu Haruna (Science Publications, 2008)
The identification and understanding of soil factors influencing yield variability of oil palm enable their efficient management. Soil samples were therefore collected from a fertilizer response trial on oil palm to study the spatial inorganic N distribution and some selected soil chemical properties as affected by long-term N fertilizer applications. The experiment was conducted on mature oil palms grown on Kumansi family (Typic Paleudults) soil in Tawau, Sabah, Malaysia. The soil samples were taken from 2 areas; with and without N treatments for 8 years. They were analyzed for total N, NH4+-N, NO3--N, exchangeable K, and pH. Semivariance analysis was used to characterize the spatial variance of soil NH4+-N and NO3--N while point kriging method was used to illustrate their spatial distributions. Results showed that application of N in the palm circle increased soil NH4+-N above 150 mg kg-1 at 0 to 15 cm depth. In unmanured plot, the NH4+-N contents were similar in the different sites within a palm area although the frond heap area tended to have higher NH4+-N probably due to the N return from the decaying cut fronds. The coefficient of variations for both soil NH4+-N and NO3--N exceeded 30% even within each microsite of palm circle, interrow, frond heaps, and harvesting path. Semivariance analysis showed that the maximum range of soil NH4+-N could be reached at 10 m and 90 m in areas with and without N respectively, indicating that the application of N fertilizer reduced its spatial variability in mature oil palm agroecosystem. The kriged soil map showed localized spots of high NH4+-N content, which corresponded to the palm circles where N fertilizer was applied. Gradual changes in soil fertility were observed in area without N, moving from northern to southern portion of the field. Long-term applications of N caused significant downward movement of NH4+-N and NO3--N to the lower soil depth. They also decreased the soil pH from 4.2 to 3.7, and caused leaching of K to the lower depth. Fertilizer should be broadcast in the interrow in mature oil palm agroecosystem to reduce spatial N variation and other detrimental effects.